Effects of fermented wheat bran and yeast culture on growth performance, immunity and intestinal microflora in growing-finishing pigs. (23rd October 2021) - He, Wei; Gao, Yanan; Guo, Zhiqiang; Yang, Zheng; Wang, Xiaoxu; Liu, Honggui; Sun, Haoyang; Shi, Baoming
Abstract: This study was conducted to evaluate the effects of feeding fermented wheat bran (FWB) and yeast culture (YC) on growth performance, immune levels and intestinal microflora in growing-finishing pigs. 96 crossbred pigs were randomly distributed into 4 treatments with 4 replicates pens and 6 pigs per pen. This study was performed using a 2×2 factor design: (1) CON (basal diet); (2) FWB (basal diet + 5% FWB); (3) YC (basal diet + 2% YC); and (4) FWB+YC (basal diet + 5% FWB + 2% YC). Dietary FWB supplementation significantly increased the average daily gain (ADG) and significantly decreased the feed gain ratio (F/G) of growing-finishing pigs ( P < 0.05). Supplementation of FWB and YC improved the immune capacity and reduced the inflammation level of growing-finishing pigs ( P < 0.05). In addition, pigs fed FWB, YC and FWB+YC diets showed better intestinal development and morphology compared with those CON pigs. The relative abundance of Streptococcus in the FWB group was significantly lower than that in the CON group ( P < 0.05), and the relative abundance of probiotics ( unclassified_f_Lachnospiraceae, Turicibacter ) increased significantly ( P < 0.05). Furthermore, the relative abundance of probiotics ( Lactobacillus, norank_f_Muribaculaceae ) in the YC group was significantly increased compared with the CON group ( P < 0.05). The results of this study observed positive influences on FWB and YC in growing-finishing pigs which provides insights for the applications of biological feed in swine industry.